Renal Cell Carcinoma Metastasizing to Left Atrium With Coronary Sinus Invasion: A Rare Site of Metastasis Mimicking Myxoma - Nkengurutse, Gerard; Wang, Qi; Tian, Feng; Jiang, Sixiong; Zhang, Liang; Sun, Weibing (Frontiers in Oncology, 2019)
Renal cell carcinoma (RCC) metastasizing to the heart with inferior vena cava (IVC) involvement is well documented. However, its metastasis to the right heart without venous involvement is very rare. To the left atrium, metastasis is even rarer with only a few cases reported in medical literature. Herein, we report a case of a 56-year-old man who presented to our department for the treatment of a right renal mass and a right adrenal mass discovered on a follow-up plain computed tomography (CT) 13 years after left laparoscopic radical nephrectomy. During the workup, a transthoracic echocardiography (TTE) revealed a left atrial mass with a suspicion of a myxoma. This finding prompted a cardiac surgery consult which proposed a surgical removal of the mass. Intraoperatively, the tumor was found to invade the coronary sinus as well. The entire tumor was successfully removed and surgical repair of the unroofed coronary sinus was performed. Pathological examination of the tumor along with immunohistochemistry – showing positivity for CAIX, CD10, Vimentin and PAX-8 – pointed to a diagnosis of metastatic clear cell RCC. Eight months postoperatively, he was free of any symptom. In conclusion, RCC metastasizing to the left atrium is extremely rare. A comprehensive search revealed only nine reports in the literature. We report, to our knowledge, the first case of RCC metastasizing to the left atrium with concomitant invasion of coronary sinus. Surgical resection combined with unroofed coronary sinus repair allowed a complete removal of the tumor. In patients with a history of RCC, a metastasis should be thought of when a left atrial mass is present.